Strategy to improve supplier performance for product competitiveness in the fried onion supply chain in Kuningan Regency - Rismayanti, Rina; S., Namira Reski Audriana; Hidayat, Yayat Rahmat (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to determine strategies that have proven to be effective in improving supplier performance. This study uses SmartPLS SEM (Partial Least Squares - Structural Equation Modeling) software for analysis. The results show that the variables of commitment, trust, information sharing, and supplier performance affect competitiveness by 0.294 (29.4%), 0.133 (13.3%), 0.587 (58.7%), respectively. Meanwhile, commitment, trusted, and information sharing affect supplier performance by 0.359 (35.9%), 0.055 (05.5%), 0.599 (59.9%) and 0.417 (41.7%), respectively. Moreover, the variable of information sharing has a significant effect on supplier performance (P0.05). This study provides valuable insights and practical recommendations for organizations looking to improve their supply chain management and strengthen supplier relationships, contributing to the broader understanding of performance optimization in supplier networks. In addition, it is also useful as a reference for fried onion suppliers in order to improve performance.